Novel aromatic polyimides derived from 2, 8-di(3-aminophenyl)dibenzofuran. Synthesis, characterization and evaluation of properties1. Issue 87 (20th September 2015) - Tundidor-Camba, Alain; Terraza, Claudio A.; Tagle, Luis H.; Coll, Deysma; Ortiz, Pablo; de Abajo, Javier; Maya, Eva M.
<x xml:space="preserve">Abstract</x> Three aromatic polyimides (PIs) were prepared from a new aromatic diamine monomer derived from the rigid ring dibenzofuran.